Uveitis Presented as a Case of Ocular Syphilis – A Rare Presentation (Journal of Medicine, 2019)
Ocular syphilis is one of the clinical presentation or complication of syphilis. Uveitis is the most common ocular diagnosis of the condition but any component of the eyes can be affected. Serology test that include both treponemal and non-treponemal antibody detections play an important role for supporting the diagnosis. This condition is considered as part of neurosyphilis and the recommended treatment follows the treatment for neurosyphilis.We reported a 47-year-old man presented with chronic episode of blurring of vision associated with floaters involving both eyes. Both eyes showed abnormal visual acuity with involvement of optic disc on the left eye. Serology tests for non-treponemal antibody and treponemal antibody test were positive. He was diagnosed as a case of bilateral posterior uveitis with left eye neuroretinitis. He was successfully treated with intravenous aqueous crystalline penicillin 3 million unit every four hour daily for 14 days.J MEDICINE JUL 2019; 20 (1) : 52-54